Peningkatan Literasi Pemasaran Digital pada Kelompok Wanita Tani Sugih Waras - Setiyani, Rahmawati; Rahmawati, Esti Dwi (Pakis Journal Institute, 2025)
Agriculture is a vital economic sector in Indonesia that plays a strategic role in providing food, creating jobs, and supporting economic growth in rural areas. Currently, the agricultural sector is not only developing in rural areas but can also develop in urban areas through the implementation of urban farming concepts and so on. Agricultural activities are not only carried out by male farmers, but women can also take part in agricultural activities through the Women's Farmers Group. The purpose of this community service activity is to improve digital marketing literacy among members of the Sugih Waras Women's Farmers Group, which is expected to increase wider market access and optimize production aspects to increase product competitiveness and thus improve the welfare of members. The partner in this community service activity is the Sugih Waras Women's Farmers Group. The community service activity was carried out by delivering materials related to agricultural commodity production and digital marketing literacy, followed by interactive discussions and activity evaluations. The results of the community service activity indicate that the digital marketing literacy improvement activity in the Sugih Waras Women's Farmers Group has succeeded in increasing the knowledge of the members of the Sugih Waras Women's Farmers Group. The members of the Sugih Waras Women's Farmers Group are committed to continuing the activity to support food security.